Kesejahteraan Maqasid Syariah: Investigasi Perilaku Keuangan Masyarakat Desa - Hana, Kharis Fadlullah; Andriasari, Widi Savitri (BISNIS, 2023)
Indonesia is a country with the largest Muslim population in the world with different tribes and ethnicities. This makes local traditions still very strong, resulting in different financial behaviors of the community. However, Indonesia's society is ranked highest globally in online gambling because it has not been able to control its financial behavior. The purpose of this study was to investigate the factors that influence the welfare of rural Muslim communities through financial behavior, financial attitudes, biases and financial decisions. The research method used is a mix method with a constructivism paradigm. The respondents of this study were 307 from various levels of society in various villages. The researcher conducted an analysis through SEM SmartPLS by testing the predictions of welfare theory in the perspective of maqasid sharia. The results showed that it was proven that community welfare in terms of maqasid sharia was directly influenced by financial behavior, attitudes and biases. However, indirectly through financial decisions the hypothesis in this study was rejected. As the highest indicator of each variable, respondents felt the need to set aside funds for investment, were aware of the importance of financial planning, and the occurrence of illusion of control bias in financial decision making. This means that on average respondents felt they had the ability to control their finances. In fact, such attitudes are indications experienced by gamblers. This shows that the indicator of speculation is a fairly dominant attitude possessed by the average respondent. This research recommendation needs to provide in-depth financial bias behavior education to the community in order to foster awareness to receive information comprehensively and minimize feelings of being able to control financial events.